2017
DOI: 10.1007/s10530-017-1437-x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the introduction history of an invasive fish predator in South Africa

Abstract: The Largemouth Bass (Micropterus salmoides) is a global invader with demonstrated ecological impacts on native fish communities. Introductions of fishes in freshwater ecosystems are often characterized as complex processes, yet an understanding of the nature of the introduction can inform management and conservation actions. Early in the twentieth century, two introductions of Largemouth Bass were made into South Africa for the establishment of a recreational fishery, and subsequent translocations have expande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…In an assessment of the parasitism of largemouth bass for example, Truter et al (2017) documented lower parasite abundance and richness in South Africa in comparison with native range populations. This may explain why this species managed to invade a wide range of habitats throughout southern Africa despite extremely low genetic diversity, resulting from a very limited number of propagules introduced into South Africa in the late 1920s (Hargrove et al 2017). Similar mechanisms might be responsible for the success of rainbow trout, Onchorhynchus mykiss, and brown trout, Salmo trutta, for which there are no records of co-introduced parasites (see Weyl et al 2020, Sect.…”
Section: Freshwater Fishmentioning
confidence: 99%
“…In an assessment of the parasitism of largemouth bass for example, Truter et al (2017) documented lower parasite abundance and richness in South Africa in comparison with native range populations. This may explain why this species managed to invade a wide range of habitats throughout southern Africa despite extremely low genetic diversity, resulting from a very limited number of propagules introduced into South Africa in the late 1920s (Hargrove et al 2017). Similar mechanisms might be responsible for the success of rainbow trout, Onchorhynchus mykiss, and brown trout, Salmo trutta, for which there are no records of co-introduced parasites (see Weyl et al 2020, Sect.…”
Section: Freshwater Fishmentioning
confidence: 99%
“…These specific sampling sites, however, often display much lower levels of genetic variability when compared to rivers, as suggested by our results (localities BU and MP in the invasive range). Similarly, a recent study reconstructing the invasion history of the largemouth bass, Micropterus salmoides , identified extremely low levels of neutral genetic diversity within invasive populations in lentic environments with limited connectivity (Hargrove, Weyl, & Austin, 2017). Their results revealed that all lentic populations had allele frequencies dominated by a single allele, but that a population sampled from Kowie Weir, located at the end of a 580 km 2 catchment, was more diverse, suggesting multiple introduction events or hybridization between co‐occurring Micropterus species (Hargrove et al., 2017).…”
Section: Discussionmentioning
confidence: 97%
“…However, sampling problems such as the number of native versus invasive populations sampled and the number of individuals sampled per population may hinder the accuracy of the molecular markers to identify the source population . To date, however, no study has looked at the effect that identified extremely low levels of neutral genetic diversity within invasive populations in lentic environments with limited connectivity (Hargrove, Weyl, & Austin, 2017). Their results revealed that all lentic populations had allele frequencies dominated by a single allele, but that a population sampled from Kowie Weir, located at the end of a 580 km 2 catchment, was more diverse, suggesting multiple introduction events or hybridization between co-occurring Micropterus species (Hargrove et al, 2017).…”
Section: The Influence Of Sampling Design On Genetic Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In southern Africa, for example, populations of Largemouth Bass were first established in the late 1920s (Harrison ; Hargrove et al. ) and became widespread by the 1930s (Ellender and Weyl ); competitive fishing events are now routinely held in Botswana, Namibia, Mozambique, South Africa, and Zimbabwe (Hargrove et al. ).…”
mentioning
confidence: 99%